Industrial policy, innovation, and complexity comparative analysis, trends, and prospects - Varsakelis, Nikolaos 1959-; Varsakelis, Nikolaos 1959-; Zarotiadis, Grigorios 1972-; Zarotiadis, Grigorios 1972-; Tzouvelekas, Manolis D. 1972-; Tzouvelekas, Manolis D. 1972- (e-Book Collection, 2026)
"This book aims to bring together diverse perspectives and in-depth analyses from scholars, policymakers, and practitioners on the current state and future directions of industrial policy in complex economies"-- Provided by publisher.